Some features of the phonetic and grammatical structure of Baca - Jordan, A C (African Languages and Literatures, 2016)
As the title implies, at this stage I am not embarking on a complete text-book of Baca, but am attempting to make an exposition of those phonetic and grammatical features of Baca that are not shared with standard Zulu and standard Xhosa. Stress has therefore been laid on the differentiae of Baca. My investigation reveals that the most remarkable differences are practically phonological and morphological, and that syntactical differences are practically negligible in quantity. For this reason, no section of this dissertation is devoted to syntax as such.